Penicillin encephalopathy. Issue 518 (December 1968) - Conway, N.; Beck, E.; Somerville, Jane
Abstract : Five patients who developed characteristic myoclonic twitching, drowsiness and convulsions due to intravenous penicillin and cloxacillin are described. Three had poor renal function. Twenty-three reported cases of penicillin encephalopathy are reviewed and the aetiology of the syndrome is discussed.